2021
DOI: 10.1590/1414-431x2020e10940
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circEGFR regulates tumor progression via the miR-106a-5p/DDX5 axis in colorectal cancer

Abstract: Recently, an increasing number of studies have reported that dysregulation of circular RNA (circRNA) expression plays critical roles in the progression of several cancers, including colorectal cancer (CRC). However, the detailed molecular mechanisms of circRNAs involvement in CRC remain largely unknown. Here, we confirmed that the level of circEGFR was significantly increased in CRC tissues compared to matched adjacent non-tumor tissues, and a high level of circEGFR was correlated with poor clinicopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Examination of miRNAs for specific fractions can significantly increase both the sensitivity and specificity of selected circulating miRNAs as noninvasive biomarkers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…Examination of miRNAs for specific fractions can significantly increase both the sensitivity and specificity of selected circulating miRNAs as noninvasive biomarkers [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Circulating Mirnamentioning
confidence: 99%
“…Many studies of cancer reported that miR-106a-5p was overexpressed in tumor and diminished GASL1's roles in cell proliferation and metastasis. Whereas GASL1 inhibited GC cell proliferation and metastasis via targeting and blocking PI3K/AKT ras/raf/MEK/ERK pathways [13][14][15] indicating role of miR-106a-5p as tumor oncogene. miR-106a-5p up-regulation is strongly correlated with invasion, lymphatic and distant metastasis, tumor stage, size, and differentiation [16].…”
Section: Discussionmentioning
confidence: 99%
“…The most overexpressed candidate, particularly in GBM-REC tumors, is circEGFR. CircEGFR is derived from the EGFR gene which is a well-established oncogene in various cancers [66, 67]. In contrast, circEFGR was also found as an inhibitor of the malignant progression of glioma by regulating the levels of miR-183-5p and TUSC2 [68].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%